Candyfloss - Wilson, Jacqueline; Illustrated by Sharratt, Nick (London Random House Children's Book, 2006)
When her mother plans to move to Australia with her new husband and baby, Floss must decide whether her loyalties lie with her mother or her father, while at the same time, her best friend begins to make fun of her and reject her.
Include illustrations
Keywords: Fathers and daughters -- England -- Friendship